Improvement of Workstation to Decrease the Muscle Pain in the Silk Weaving Preparation Process at the Weaving Group in Surin Province - Rithinyo, Manote; Nithikarnjanatharn, Jittiwat; Mayai, Amornsak; Loatong, Poranee (Journal of Advanced Development in Engineering and Science, 2023)
The inappropriate ergonomic designs of workstation and work posture lead to the problem about the musculoskeletal system and muscles of workers. This became the important problem affecting the production efficiency. This study aims to improve the workstation to decrease the muscle pain in the silk weaving preparation process at the weaving group in Surin province. The ECRS (Eliminate, Combine, Rearrange, Simplify) technique was used as tool to improve the workstation with purpose to find out the Abnormality index (AI) and Electromyography (EMG) based on the Mean Frequency. The result of the study found that the improvement could reduce the Abnormal Index of the sample groups who were 25-39, 40-49, 50-59 and more than 60 years old at the percentage of 41.77, 40.41, 41.39 and 42.97 respectively. The comparison of the Abnormality index (AI) using the Electromyography (EMG) focusing on the average rate of Erector Spinae and Trapezius muscle at work prior and after the improvement found that the average rate of muscle after the improvement was less than prior the improvement. Moreover, the improvement could reduce the time for silk weaving preparation process at 65.06%.